IMPROVING STUDENTS’ VOCABULARY MASTERY USING CARD SORT (AN ACTION RESEARCH AT SD NEGERI 2 KLEWOR KEMUSU BOYOLALI) - WIDATI, FITRI WAHYU (2010)
This research aims at (1) describing the implementation of teaching vocabulary using card sort at SD N 2 Klewor Kemusu Boyolali and (2) knowing the result of teaching vocabulary using card sort. This study constitutes an action research classroom. Card sort was applied to solve the problems faced by the students, namely planning, acting, observation and reflection. In collecting the data, the writer used observation and documentation. Teaching speaking in SD N 2 Klewor Kemusu Boyolali uses card sort. This is collaborative activity that is able to be applied in teaching concepts, categorizing characteristics, fact of object, recalling information. The results of the research show that: the result of pre-test was very low. It is caused by the use of teaching method which was not interesting for the students. The average score of pre test is 56.87. The highest score is 85 and the lowest score is 30. Then, the writer implemented an action research by using card sort to increase student’s vocabulary mastery which consists of planning, implementing, observing and reflecting. In cycle I there ware many students who get bad score. It can be seen from the score of post test of cycle I, the average score of is 71.56, the highest score is 100 and the lowest score is 45. It means that the writer should implement card sort in cycle 2. In cycle II, the score of student’s vocabulary mastery is increase. It can been seen from the the score of post test cycle II, the average score of cycle 2 is 81.87, the highest score is 100 and the lowest score is 60. From the result above, it can be concluded that teaching vocabulary by using card sort improve students’ vocabulary mastery.